A regularized trace formula for second order differential operator equations - Koklu, Kevser; Albayrak, Inci; Bayramov, Azad (MATHEMATICA SCANDINAVICA, 2010)
In this paper, we deal with abstract Sturm-Liouville problems when the potential of the differential equation is an operator function in a Hilbert space H. We generalize trace formula obtained by [7], [9] for the classic regular Sturm-Liouville problems. We investigate the spectrum and obtained a regularized trace formula for the Sturm-Liouville operator with an operator coefficient.